Teologi Politik Paulus sebagai Respons terhadap Konflik Ideologi dan Kepatuhan Hukum Taurat pada Jemaat Galatia - Christiaan, John Abraham; Manuputty, Mozes (KHAMISYIM: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This article examines the political theology of the Apostle Paul in the Letter to the Galatians as a response to the ideological conflict that arose from the insistence of the Judeo-Christian group that non-Jewish congregations obey the Law of Moses. In the pluralistic socio-political context of the province of Galatia, which was under Roman rule, religious identity became a battleground between loyalty to Jewish law and new freedom in Christ. Through a historical-theological approach and narrative analysis, this article asserts that Paul not only defended his apostolic authority but also shaped a vision of a transnational community that transcended ethnic and legal boundaries, grounded in love and freedom in the Spirit. Paul's political theology serves as a sharp critique of exclusive ideologies that enslave people, while simultaneously offering an alternative inclusive and eschatological community in Christ. AbstrakArtikel ini mengkaji teologi politik Rasul Paulus dalam Surat Galatia sebagai respons terhadap konflik ideologis yang muncul akibat desakan kelompok Yudeo-Kristen agar jemaat bukan Yahudi menaati Hukum Taurat. Dalam konteks sosial-politik provinsi Galatia yang plural dan berada di bawah kekuasaan Romawi, identitas keagamaan menjadi medan tarik menarik antara kesetiaan kepada hukum Yahudi dan kebebasan baru dalam Kristus. Melalui pendekatan historis-teologis dan analisis naratif, artikel ini menegaskan bahwa Paulus tidak hanya membela otoritas kerasulannya, tetapi juga membentuk suatu visi komunitas transnasional yang melampaui batas-batas etnis dan hukum, berlandaskan kasih dan kebebasan dalam Roh. Teologi politik Paulus menjadi kritik tajam terhadap ideologi eksklusif yang membelenggu umat dan sekaligus menawarkan alternatif komunitas yang inklusif dan eskatologis dalam Kristus. Kata Kunci: Paulus, Teologi Politik, Galatia, Hukum Taurat